(untitled) (Journal of Applied Oral Science, 2010)
OBJETIVES: The aim of this study was to investigate through scanning electron microscopy (SEM) the cleaning of root canal walls after the use of experimental propolis or calcium hydroxide root canal dressings. MATERIAL AND METHODS: Twenty single-rooted teeth were used. After conventional cleaning and shaping procedures and removal of the smear layer with 17% EDTA, the teeth were divided into four groups according to the medication used (N=5): Group I (control) - No drug, Group II - Calcium hydroxide dressing, Group III - Propolis paste A70D and Group IV - Propolis paste D70D. The medications were introduced into the root canals and maintained for 7 days, then removed with a K-file and 5 mL of 1% sodium hypochlorite irrigation. Finally, the canals were flushed with 2 mL of 17% EDTA for 3 min. For SEM analysis, the roots were cleaved and microphotographs from the middle third of the root canal were taken at 750x. The cleaning of the root canal walls was determined by the number of open dentinal tubules as verified with the software Image Tool 3.1. The statistical analysis was performed by ANOVA and Tukey's test (p